Low level aflatoxin exposure associated with greater linear growth in southern Mexico: A longitudinal study - Leroy, Jef L.; Sununtnasuk, Celeste; Garcia-Guerra, Armando; Wang, Jia-Sheng (Wiley, 2018)
Aflatoxins are a group of naturally occurring mycotoxins, which can lead to death and are a known cause of hepatocellular carcinoma. AF exposure has been hypothesised to lead to stunted growth in children, but separating the AF effect from other determinants of linear growth retardation is difficult. The study used secondary data from an efficacy trial conducted in young children in southern Mexico to test the comparative efficacy of a milk‐based multiple micronutrient‐fortified food, a multiple micronutrient syrup, or a multiple micronutrient powder. The effect of serum AFB1‐lysine adduct level on incremental growth was tested using a longitudinal mixed model, controlling for key individual, maternal, and household‐level covariates. AFB1‐lysine adduct was detectable in all but 2 of the 347 children in the study (median exposure: 0.82 pg/mg albumin). AF exposure was associated (p < .05) with greater linear growth: an increase equivalent to the sample interquartile range (~0.5 pg AFB1‐lysine/mg albumin) was associated (p < .05) with an increase in the child's height‐for‐age deficit of 1.5 to 2.0 mm in the 4 months from baseline (average age 8 months) to follow‐up (average age 12 months); the magnitude of the difference in the 10‐month follow‐up was smaller and not statistically significant. This study documents that low‐dose AF exposure was associated with greater child linear growth. Given its toxicity and carcinogenicity, our results do not change the urgent need to drastically reduce human AF exposure. Our findings show that the association between AF exposure and linear growth is more complex than previously thought.